Deal or no deal? The prevalence and nutritional quality of price promotions among U.S. food and beverage purchases. (1st October 2017) - Taillie, Lindsey Smith; Ng, Shu Wen; Xue, Ya; Harding, Matthew
Abstract: Objective: This study examines trends in the prevalence of price promotions among packaged food and beverage purchases, differences in prevalence by household race/ethnicity or income, and the association between price promotions and the nutritional profile of purchases. Design: This cross-sectional study utilizes a dataset of 90 million purchases from 38, 744 (2008) to 45, 042 (2012) US households in 2008–2012. Chi-square tests were used to examine whether the proportion of purchases with price promotions changed over time or differed by household race/ethnicity or income. T-tests were used to compare purchased products' nutritional profiles. Results: Prevalence of price promotions among packaged food and beverage purchases increased by 8% and 6%, respectively, from 2008 to 2012, with both reaching 34% by 2012. Higher-income households had greater proportions of purchases with price promotions than lower-income households. Asian households had the highest proportion of purchases with any price promotion, followed by non-Hispanic whites. While total price-promoted packaged food purchases had higher mean energy, total sugar, and saturated fat densities than purchases with no price promotions, absolute differences were small. Conclusions: Prevalence of price promotions among US household purchases increased from 2008 to 2012 and was greater for higher-income households. No clear associations emerged between presence of price promotions and nutritional quality of purchases.